Ultrathin dual-mode vortex beam generator based on anisotropic coding metasurface - Liang Zhang (Nature Portfolio, 2021)
Abstract In this paper, an anisotropic coding metasurface is proposed to achieve dual-mode vortex beam generator by independently manipulating the orthogonally linearly polarized waves. The metasurface is composed of ultrathin single-layer ground-backed Jerusalem cross structure, which can provide complete and independent control of the orthogonally linearly polarized incident waves with greatly simplified design process. As proof of concept, a metasurface is designed to generate vortex beams with different topological charges under orthogonal polarizations operating at 15 GHz. Experimental measurements performed on fabricated prototype reveal high quality, and show good agreements with theoretical designs and simulation results. Such ultrathin dual-mode vortex beam generator may find potential applications in wireless communication systems in microwave region.